Leakage-Based Precoder Optimization and Deep Unfolding for User-Centric Cell-Free Massive MIMO - Xu, Chunmei; Zhang, Cheng; Huang, Yongming; Wu, Yi; Lu, Zhaohua (IEEE transactions on vehicular technology, 2025)
This article investigates the leakage-based precoder design for user-centric cell-free massive MIMO systems. Given the clustered APs for each UE, the problem is formulated as a group sparse optimization to maximize the leakage rate under per-AP power constraints. Its equivalent formulation is derived by introducing two auxiliary variables. An iterative optimization method (IOM) is proposed based on block coordinate descent and bisection search techniques, which converges to a stationary solution. To reduce the required computations, a deep unfolding-based method (DUBM) is developed to unfold the iterative procedure of IOM via the proposed neural network layer. Simulation results demonstrate the competitive performance of the proposed methods, with IOM achieving higher sum-rates while DUBM providing higher computational efficiency compared to the reference methods.